Molecular marker dissection of stem rust resistance in Nebraska bread wheat germplasm - Amira M. I. Mourad (Nature Portfolio, 2019)
Abstract Stem rust (caused by Puccinia graminis f. sp. tritici) is a major disease of wheat. To understand the genetic basis of stem rust resistance in Nebraska winter wheat, a set of 330 genotypes representing two nurseries (DUP2015 and TRP2015) were evaluated for resistance to a Nebraska stem rust race (QFCSC) in two replications. The TRP2015 nursery was also evaluated for its resistance to an additional 13 stem rust races. The analysis of variance revealed significant variation among genotypes in both populations for stem rust resistance. Nine stem rust genes, Sr6, Sr31, Sr1RS Amigo , Sr24, Sr36, SrTmp, Sr7b, Sr9b, and Sr38, were expected and genotyped using gene-specific markers. The results of genetic analysis confirmed the presence of seven stem rust resistance genes. One genotype (NE15680) contained target alleles for five stem rust resistance genes and had a high level of stem rust resistance against different races. Single marker analysis indicated that Sr24 and Sr38 were highly significantly associated with stem rust resistance in the DUP2015 and TRP2015 nurseries, respectively. Linkage disequilibrium analysis identified the presence of 17 SNPs in high linkage with the Sr38-specific marker. These SNPs potentially tagging the Sr38 gene could be used in marker-assisted selection after validating them in additional genetic backgrounds.